1995
DOI: 10.1104/pp.109.2.549
|View full text |Cite
|
Sign up to set email alerts
|

Tonoplast Na+/H+ Antiport Activity and Its Energization by the Vacuolar H+-ATPase in the Halophytic Plant Mesembryanthemum crystallinum L

Abstract: Tonoplast vesicles were isolated from leaf mesophyll tissue of the inducible Crassulacean acid metabolism plant Mesembryanfbemum crystallinum to investigate the mechanism of vacuolar Na+ accumulation in this halophilic species. In 8-week-old plants exposed to 200 mM NaCl for 2 weeks, tonoplast H+-ATPase activity was approximately doubled compared with control plants of the same age, as determined by rates of both ATP hydrolysis and ATP-dependent H+ transport. Evidence was also obtained for the presence of an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(99 citation statements)
references
References 32 publications
11
88
0
Order By: Relevance
“…60,61 It has been shown that the transcript levels of some subunits are upregulated in response to salt stress. In fully expanded leaves of M. crystallinum, 8 h after salt treatment, there was an increase in the transcript levels of subunit c mRNA but not of subunit A or B, 62 which correlates well with the observed increase in activity of the V-H + -ATPase in vesicles from leaf mesophyll tissue from plants treated with salt, 51 whereas in roots and young leaves, mRNA levels for all the three subunits increased about 2-fold compared to control plants. The expression of vacuolar H + -ATPase genes does not always involve a fixed stoichiometry of mRNAs for the different subunits and the mRNA level for subunit c is particularly sensitive to developmental and environmental changes.…”
Section: Regulation Of V-h + -Ppase and V-h + -Atpase Activity By Saltsupporting
confidence: 54%
See 1 more Smart Citation
“…60,61 It has been shown that the transcript levels of some subunits are upregulated in response to salt stress. In fully expanded leaves of M. crystallinum, 8 h after salt treatment, there was an increase in the transcript levels of subunit c mRNA but not of subunit A or B, 62 which correlates well with the observed increase in activity of the V-H + -ATPase in vesicles from leaf mesophyll tissue from plants treated with salt, 51 whereas in roots and young leaves, mRNA levels for all the three subunits increased about 2-fold compared to control plants. The expression of vacuolar H + -ATPase genes does not always involve a fixed stoichiometry of mRNAs for the different subunits and the mRNA level for subunit c is particularly sensitive to developmental and environmental changes.…”
Section: Regulation Of V-h + -Ppase and V-h + -Atpase Activity By Saltsupporting
confidence: 54%
“…24 A general sodium-induced increase in V-H + -ATPase activity in plant response to salt has been reported. 35,37,38,41,42,44,45,47,[49][50][51][52][53][54][55][56] In contrast, the activity of V-H + -ATPase in Daucus carrota was unaffected by salt treatment 43 and was even repressed in wheat roots under severe NaCl stress. 40 In the halophyte S. salsa, the main strategy of salt-tolerance seems to be an upregulation of V-H + -ATPase.…”
Section: Regulation Of V-h + -Ppase and V-h + -Atpase Activity By Saltmentioning
confidence: 99%
“…Stress-induced changes in tonoplast ATP synthase activity and gene expression have recently been reported for this plant (Löw et al, 1996;Tsiantis et al, 1996). Also, tonoplast Na ϩ /H ϩ antiport activity increases during stress (Barkla et al, 1995). Amounts of water channel transcripts and of some water channel proteins respond to salinity stress (Yamada et al, 1995;H.…”
Section: Discussionmentioning
confidence: 99%
“…The homogenization medium consisted of 400 mM mannitol, 10% (w/v) glycerol, 5% (w/v) PVP-10, 0.5% (w/v) BSA, 1 mM PMSF, 30 mM Tris, 2 mM DTT, 5 mM EGTA, 5 mM MgSO 4 , 0.5 mM butylated hydroxytoluene, 0.25 mM dibucaine, 1 mM benzamidine, and 26 mM K + -metabisulfite, adjusted to pH 8.0 with H 2 SO 4 . Microsomal membranes and tonoplast were isolated as previously described (Barkla et al, 1995). Membranes were frozen directly in liquid N 2 and stored at 2808C.…”
Section: Microsomal Membrane Isolationmentioning
confidence: 99%
“…In both salt-tolerant halophytes and salt-sensitive glycophytes, sodium regulates the expression at the transcript and protein levels for the tonoplast NHXs (Shi and Zhu, 2002;Yokoi et al, 2002) and different subunits of the V-ATPase Tsiantis et al, 1996;Dietz et al, 2001;Vera-Estrella et al, 2005). In addition, their transport activity has been shown to increase under salt stress (Reuveni et al, 1990;Barkla et al, 1995;Qiu et al, 2004;Vera-Estrella et al, 2004). In Arabidopsis thaliana, mutants of NHX family members displayed enhanced salt sensitivity (Shi et al, 2000;Apse et al, 2003), as do mutants in subunits of the V-ATPase.…”
Section: Introductionmentioning
confidence: 99%